Rate of Reinfection Tuberculosis after Successful Treatment Is Higher than Rate of New Tuberculosis - Verver, Suzanne; Warren, Robin M; Beyers, Nulda; Richardson, Madalene; van der Spuy, Gian D; Borgdorff, Martien W; Enarson, Donald A; Behr, Marcel A; van Helden, Paul D (American journal of respiratory and critical care medicine, 2005)
In a high-tuberculosis (TB) incidence area of Cape Town, South Africa, there is a very high rate of unexplained recurrent TB. The incidence of new bacteriologically confirmed disease in the area is 313 per 100,000 individuals. To estimate the rate of recurrent TB attributable to reinfection after successful treatment. All patients with reported TB in the area between 1993 and 1998 were followed up to 2001 for disease needing retreatment (recurrences). Patients who were multi-drug-resistant or who had treatment failure, were transferred, or died during treatment were excluded. Analysis was restricted to patients for whom DNA fingerprinting of their Mycobacterium tuberculosis isolates was obtained. Reinfection TB was defined as a recurrent TB episode in which the strains of the separate episodes differed by more than four bands. 612 of 897 (68%) patients had a DNA fingerprint available at enrollment. Median duration of follow-up was 5.2 years. Recurrent TB occurred in 108 of 612 (18%) patients, of whom 61 of 447 (14%) experienced recurrence after successful treatment, and 47 of 165 (28%) experience recurrence after default. Of the 108 patients with recurrent TB, 68 (63%) had a DNA fingerprint in the second episode. Among these patients, 24 of 31 (77%) recurrences after successful treatment and 4 of 37 (11%) recurrences after default were attributable to reinfection. The reinfection disease rate after successful treatment was estimated at 2.2 per 100 person-years. The age-adjusted incidence rate of TB attributable to reinfection after successful treatment was four times that of new TB. People who had TB once are at a strongly increased risk of developing TB when reinfected.